2022
DOI: 10.1097/ta.0000000000003583
|View full text |Cite
|
Sign up to set email alerts
|

Emergency department return visits and hospital admissions in trauma team assessed patients initially discharged from the emergency department: A population-based cohort study

Abstract: Our study looks at the outcomes of trauma patients discharged home from the ED. We found that nearly one in five patients returned within two weeks but that serious diagnoses or surgical interventions were very rare. Several patient characteristics predicted return visits.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…In a recent Canadian study, it was reported that 18% of their trauma population had at least one ED return visit within 2 weeks, 24 in contrast to older studies that have reported 14% re-attendance over a 30-day follow-up period. 25,26 The cohort of patients with blunt chest trauma in our study demonstrated an 18% unplanned re-attendance rate at the ED within 12 weeks.…”
Section: Discussionmentioning
confidence: 86%
“…In a recent Canadian study, it was reported that 18% of their trauma population had at least one ED return visit within 2 weeks, 24 in contrast to older studies that have reported 14% re-attendance over a 30-day follow-up period. 25,26 The cohort of patients with blunt chest trauma in our study demonstrated an 18% unplanned re-attendance rate at the ED within 12 weeks.…”
Section: Discussionmentioning
confidence: 86%
“…ICES data sets used in this study include the Registered Persons Database for demographic information and vital status, the Ontario Trauma Registry (OTR) for injury information, the Canadian Institute of Health Care Information Discharge Abstract Database for further inpatient diagnostic and procedural information and comorbidities (measured with the Elixhauser Comorbidity Index score, 18,19 3-year look-back period), and the Ontario Mental Health Reporting System for mental health admissions, as well as the National Ambulatory Care Reporting System and OHIP for outpatient mental health service provided by emergency physicians or family physician or psychiatrists, respectively (Supplementary Digital Content, Supplementary Table 1, http://links.lww.com/TA/C752). ICES databases have previously been shown to be inclusive of our province's entire emergency system (covering >99% of emergency departments) and to have high data linkage rates (>95%) and internal diagnostic validity (>90% compared with medical record abstraction) 20–23 …”
Section: Methodsmentioning
confidence: 99%
“…ICES databases have previously been shown to be inclusive of our province's entire emergency system (covering >99% of emergency departments) and to have high data linkage rates (>95%) and internal diagnostic validity (>90% compared with medical record abstraction). [20][21][22][23]…”
Section: Settingmentioning
confidence: 99%